Post a New Question

trig

posted by on .

Prove that tan4x=(4tanx-tan^3x)/(1-6tan^2 x+tan^4 x)
*note: the exponents are just numbers. there are no variables in the exponents.

  • trig - ,

    ukgggg

  • trig - ,

    we know tan2A= 2tanA / 1-tan2A

    using this formula,

    tan4x = tan2.(2x)

    =2tan2x / 1-tan22x

    = 2(2tanx/1-tan2x) / 1-(2tanx/{1-tan2x}2)

    simplify to get. , 4tanx(1-tan2x) / 1-6tan2x+tan4x.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question